Multiple Export Mechanisms for mRNAs - Delaleau, Mildred (Cells, 2015)
Nuclear mRNA export plays an important role in gene expression. We describe the mechanisms of mRNA export including the importance of mRNP assembly, docking with the nuclear basket of the nuclear pore complex (NPC), transit through the central channel of the NPC and cytoplasmic release. We describe multiple mechanisms of mRNA export including NXF1 and CRM1 mediated pathways. Selective groups of mRNAs can be preferentially transported in order to respond to cellular stimuli. RNAs can be selected based on the presence of specific cis-acting RNA elements and binding of specific adaptor proteins. The role that dysregulation of this process plays in human disease is also discussed.